The Development of Transformation Geometry Learning Medium with Scientific Approach As Effort to Improve the Understanding Concept Skill - Wirapathi, Agung; Candiasa, Made; Suryawan, Pasek (Journal of Education Technology, 2018)
"> The development research aims to describe: (1) storyboard; (2) the implementation results; and (3) the usability of thetransformation geometry learning medium with scientific approach. The development uses 4-D model which consisting ofdefine, design, develop, and disseminate, but this research is only up to the develop step. The results showed that thetransformation geometry learning medium with scientific approach can be accepted as a learning medium with very validcategory, which seen from the validity score is 4.37. Learning medium developed got excellent response with the averagescore of practicability is 4.5. This learning medium also has a high effectiveness in learning process with the level of studentactivity reached the average score around 4.2, and the classical completeness is 80%. Based on the result of the research, itâsexpected that the transformation geometry learning medium with scientific approach can be used in learning process.